Evaluating Intangible Cultural Heritage Policy of Balinese Handwoven Textiles - Parameswara, Agung (Mudra Jurnal Seni Budaya, 2024)
Several key factors drive contemporary concerns about the sustainability of intangible cultural heritage. Cultural policy has given meaning and importance to the cultural diversity of society. However, the efforts to preserve intangible cultural heritage by providing a way to community welfare are facing new challenges. The article aims to present an analysis of local cultural policy from Bali Governance to sustain the intangible heritage of handwoven textiles by increasing the economy demand. Using a focus group approach, qualitative data were collected and using Nvivo12 to analyze the data from 15 interviews of weavers and practices of Balinese handwoven textiles living in Bali. This approach is used as a means to represent the complex diversity of opinions among members of the weaving group in a dynamic interaction that is provided so that a diversity of views emerges from the participants and direct clarification of the issues that influence the diversity of arguments on the reality of the impact on policy. The result found that the cultural policy is increasing the sense of identity by using Balinese handwoven textiles and significantly has the direct impact for the demand of handwoven textiles. Furthermore, the research revealed that cultural policy plays important role in shaping and reviving the traditional practices by evaluating the challenges of cultural industries such as industrialization, regeneration knowledge, environmental sustainability by reducing chemical dyes, the welfare of women weavers, market access and strong representation between communities.